Canine Distemper Virus (CDV): an emerging threat to Nepal’s wildlife - Adhikari, Roshan Babu; Shrestha, Mina; Puri, Ganesh; Regmi, Ganga Ram; Ghimire, Tirth Raj (Applied Science and Technology Annals, 2020)
In this article, we have described the urgency of research on CDV in the domestic and feral dogs roaming in and around the protected areas of Nepal where the already threatened wildlife have been struggling for their existence from the immense anthropogenic pressures.